2021
DOI: 10.1172/jci149335
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 mRNA vaccines induce broad CD4+ T cell responses that recognize SARS-CoV-2 variants and HCoV-NL63

Abstract: Recent studies have shown T cell cross-recognition of SARS-CoV-2 and common cold coronavirus spike proteins. However, the effect of SARS-CoV-2 vaccines on T cell responses to common cold coronaviruses remain unknown. In this study, we analyzed CD4+ T cell responses to spike peptides from SARS-CoV-2 and 3 common cold coronaviruses (HCoV-229E, HCoV-NL63, and HCoV-OC43) before and after study participants received Pfizer-BioNTech (BNT162b2) or Moderna (mRNA-1273) mRNA-based COVID-19 vaccines. Vaccine recipients m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
162
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(177 citation statements)
references
References 21 publications
12
162
0
3
Order By: Relevance
“…Considering these variants may escape antibody neutralization, how they influence the T-cell immune response is of particular interest. One published report measured CD4 T-cell vaccine responses to a subset of the mutations in the B.1.1.7 and B.1.351 variants in one of two spike protein subunits, finding no decreased response to variant relative to wild type proteins 45 . However, as the authors acknowledge, wild type responses were very low due to the use of whole proteins rather than peptide pools 45 , which precludes an accurate fold-change assessment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering these variants may escape antibody neutralization, how they influence the T-cell immune response is of particular interest. One published report measured CD4 T-cell vaccine responses to a subset of the mutations in the B.1.1.7 and B.1.351 variants in one of two spike protein subunits, finding no decreased response to variant relative to wild type proteins 45 . However, as the authors acknowledge, wild type responses were very low due to the use of whole proteins rather than peptide pools 45 , which precludes an accurate fold-change assessment.…”
Section: Resultsmentioning
confidence: 99%
“…One published report measured CD4 T-cell vaccine responses to a subset of the mutations in the B.1.1.7 and B.1.351 variants in one of two spike protein subunits, finding no decreased response to variant relative to wild type proteins 45 . However, as the authors acknowledge, wild type responses were very low due to the use of whole proteins rather than peptide pools 45 , which precludes an accurate fold-change assessment. To determine the impact of these variants on the magnitude of the anti-spike T-cell response in vaccinated individuals, we used our ELISpot assay to stimulate PBMC from vaccinated individuals post-V2 with spike peptide pools from the B.1.1.7, B.1.315, and B1.1.248 SARS-CoV-2 variants ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole blood CRA and ELISPOT also showed that the region 501-705 AA contained in Pool 4 is the least immunogenic with only 1 out of the 6 vaccine recipients displaying a response at different time points (Figure 3B and C). Interestingly, analysis of individuals who recovered from SARS-CoV-2 infection (23) and in mRNA vaccine recipients (24) showed a similar reduced frequency of response in the Spike region 500-700 AA for CD4 T cells assayed through AIM detection. Taken together, these data show that direct analysis of cytokines secreted in whole blood pulsed with different peptides constitute a reliable method to gauge the presence and magnitude of functional T cells specific for epitopes covered by the utilized peptides.…”
Section: Resultsmentioning
confidence: 93%